Piezoresistive Sensors: Full 3D Printing of Stretchable Piezoresistive Sensor with Hierarchical Porosity and Multimodulus Architecture (Adv. Funct. Mater. 11/2019). (12th March 2019) - Wang, Ziya; Guan, Xiao; Huang, Huayi; Wang, Haifei; Lin, Waner; Peng, Zhengchun
Abstract : In article number1807569, Zhengchun Peng and co‐workers fabricate a stretchable piezoresistive sensor by 3D‐printing of a multilayered sensing element of a hierarchically porous structure on a pair of 3D‐printed double helix interdigital electrodes on an elastomer substrate. The three layers are composed of the same polymer matrix but with a different modulus. The sensor demonstrates high sensitivity, large measurement range, limited cross‐correlation, stable stretch resistance, and excellent durability.